A Meta-Analysis of Gifted and Talented Identification Practices. (April 2018) - Hodges, Jaret; Tay, Juliana; Maeda, Yukiko; Gentry, Marcia
Researchers consider the underrepresentation of Black, Hispanic, and Native American students is largely due to the use of traditional methods of identification (i.e., IQ and standardized achievement tests). To address this concern, researchers created novel nontraditional identification methods (e.g., nonverbal tests, student portfolios, affective checklists). This meta-analysis of 54 studies, consisting of 85 effect sizes representing 191, 287, 563 students, provides evidence that nontraditional identification methods, while able to narrow the proportional identification gap between underrepresented (Black, Hispanic, and Native American) and represented (Asian and White American) populations, are still unable to address the issue of education inequity. An overall risk ratio of 0.34 was calculated for nontraditional methods of identification in comparison with a 0.27 risk ratio for traditional methods. While the nontraditional methods help identify more underrepresented students as gifted, the results of this meta-analysis show that better identification methods are needed to address inequities in identification.